2004
DOI: 10.1152/ajpregu.00222.2004
|View full text |Cite
|
Sign up to set email alerts
|

Contractile properties of human placental anchoring villi

Abstract: The presence of myofibroblasts arranged parallel to the longitudinal axes of anchoring villi of the placenta has previously been described. Furthermore, it has been suggested that intraplacental blood volume, and hence fetal-maternal oxygen-nutrient exchange, may in part be regulated through the longitudinal contraction of anchoring villi. We demonstrate here that anchoring villi have the ability to contract and relax longitudinally. Anchoring villi from normal term human placentae were dissected and suspended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…SMC or myofibroblasts form a clearly-defined, perivascular contractile sheath previously demonstrated in large stem villi [Graf et al, 1994] and anchoring villi [Farley et al, 2004], and it was suggested that the contraction of these cells adjusts the blood flow in fetal vessels and increases the turgor, imparting mechanical stability to the villous tree in the maternal blood stream. Moreover, contraction of longitudinally-arranged myofibroblasts within anchoring villi may influence the length and width of the intervillous space, thus regulating maternal intervillous blood pressure [Graf et al, 1994;Farley et al, 2004]. The stimulus for this type of contraction is not yet established because the placenta is a non-innervated organ.…”
Section: Telocytes and Blood Flow Regulationmentioning
confidence: 98%
See 1 more Smart Citation
“…SMC or myofibroblasts form a clearly-defined, perivascular contractile sheath previously demonstrated in large stem villi [Graf et al, 1994] and anchoring villi [Farley et al, 2004], and it was suggested that the contraction of these cells adjusts the blood flow in fetal vessels and increases the turgor, imparting mechanical stability to the villous tree in the maternal blood stream. Moreover, contraction of longitudinally-arranged myofibroblasts within anchoring villi may influence the length and width of the intervillous space, thus regulating maternal intervillous blood pressure [Graf et al, 1994;Farley et al, 2004]. The stimulus for this type of contraction is not yet established because the placenta is a non-innervated organ.…”
Section: Telocytes and Blood Flow Regulationmentioning
confidence: 98%
“…To ascertain a possible role(s) for TC in the physiology of the placenta, we focused on the distribution of presumed TC in the villous core and on their interaction with surrounding stromal cells and the perivascular contractile sheath [Graf et al, 1995;Farley et al, 2004], a structure involved in fetal blood flow regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The second type of contractile system consists of non-muscle structures whose contractile properties appear most often during pathological states, such as in skin after an injury, during repair and healing processes, and in fibrotic diseases. In a physiological state, the normal human placenta consists of non-muscle contractile tissues [2,3]. The non-muscle basic contractile cell is the myofibroblast [4] and the molecular motor is the non-muscle myosin type II (NMII) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In human placental vessels, NO maintains low basal tone and attenuates the vasoconstrictor effects of thromboxane and endothelin, thereby contributing to the adequate transfer of nutrients and oxygen to the fetus (Myatt et al 1992;Farley et al 2004).…”
Section: Introductionmentioning
confidence: 99%